Comparison of patient outcomes in academic medical centers with and without value analysis programs - Murray AS; Griswold M; Sunesara I; Smith E (Dove Medical Press, 2012)
Adrienne S Murray, Michael Griswold, Imran Sunesara, Ed SmithUniversity of Mississippi Health Care, University of Mississippi Medical Center, Jackson, MS, USABackground: Value analysis is the science of balancing the mandate to deliver high-quality clinical outcomes with the necessity to drive down costs in order to thrive in the challenging economics of health care. This study compared average length of stay, direct cost, morbidity, and mortality across the cardiology, cardiovascular, neuroscience, and orthopedic service lines, in academic medical centers with and without value analysis programs (VAPs). The basic question was, “Do academic medical centers with VAPs have lower average length of stay, better morbidity and mortality rates, and lower overall supply costs?”Methods and results: The clinical data base/resource manager (CDB/RM) of the University HealthSystem Consortium was utilized as secondary data for this study. Reports from the CDB/RM were generated from 2006 to 2011. Continuous variable differences across VAP status were examined using Wilcoxon two-sample tests. Primary analyses used multilevel linear mixed model methods to estimate the effects of VAPs on primary outcomes (average length of stay, cost, morbidity, mortality). Association components of the linear mixed models incorporated random effects at the hospital level and robust, Huber-White, standard errors were calculated. There was no significant difference for average length of stay, direct cost, morbidity, and mortality between academic medical centers with and without VAPs. However, outcomes were not noted to be substantially worse.Conclusion: Numerous case studies reveal that aggressively active VAPs do decrease hospital cost. Also, this study did not find a negative impact on patient care. Further studies are needed to explore the benefits of value analysis and its effect on patient outcomes.Keywords: value analysis, average length of stay, morbidity, mortality, health care costs, supply chain